Odpowiedź :
Odpowiedź:
c) (3x-y+1) - (x+y) +(y -x) = (3•2-(-3) +1) -(2+(-3)) +(-3-2) =(6+3+1) -(-1) +5=10+1+5=16
d) -(2x² - 3xy) - (2y-3x²) +(-xy-y) = -(2•4-3•2•(-3)) - (2•(-3) - 3•4) + (-2•(-3) -(-3)) = -(8-(-18))-(-6-12)+(6+3) =-(8+18)-18+9=26-27=-1
Odpowiedź:
c) (3x - y + 1) - (x + y) + (y - x) = 3x - y + 1 - x - y + y - x = x - y +1
po doprowadzeniu do najprostszej postaci, podstawiamy:
x = 2 i y = -3
x - y + 1 = 2 - (-3) + 1 = 2 + 3 + 1 = 6
d)
-(2[tex]x^{2}[/tex] - 3xy) - (2y -3[tex]x^{2}[/tex]) + (-xy - y) = -2[tex]x^{2}[/tex] +3xy - 2y + 3[tex]x^{2}[/tex] -xy -y = [tex]x^{2}[/tex] + 2xy - 3y
podstawiamy:
x = 2 i y = -3
[tex]x^{2}[/tex] + 2xy - 3y = [tex]2^{2}[/tex] + 2* 2 *(-3) - 3*(-3) = 4 - 12 + 9 = 13 - 12 = 1
Szczegółowe wyjaśnienie: